2016
DOI: 10.1002/bit.25982
|View full text |Cite
|
Sign up to set email alerts
|

Detection of influenza virus using peroxidase‐mimic of gold nanoparticles

Abstract: A modified enzyme-linked immunosorbent assay (ELISA) with nanomaterials is an effective and powerful method to amplify the signal and reduce the cost of detecting and measuring trace biomarkers or proteins. In this study, an ultra-sensitive colorimetric immunoassay was designed, and its ability to detect influenza viruses using positively charged gold nanoparticles ((+)Au NPs) was assessed as a possible role for peroxidase-mimic inorganic enzymes. This method detected influenza virus A (H1N1) with a linear ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 21 publications
3
50
0
Order By: Relevance
“…The limit of detection (LOD) was calculated based on the standard deviation method as reported previously LOD normale3.3SDblankb…”
Section: Methodsmentioning
confidence: 99%
“…The limit of detection (LOD) was calculated based on the standard deviation method as reported previously LOD normale3.3SDblankb…”
Section: Methodsmentioning
confidence: 99%
“…Next, we attempted to detect secreted TGF-β1 from A549-CUG2 cells and BEAS-CUG2 cells in the medium, where it can be used in a paracrine or an autocrine manner. Herein, we introduced a new and verified ELISA method using gold nanoparticles which can enhance sensitivity to detect TGF-β1 as described elsewhere [27]. We found that A549-Vec cells intrinsically produce more TGF-β1 than BEAS-Vec cells.…”
Section: Resultsmentioning
confidence: 99%
“…The ELISA described elsewhere [27] was slightly modified. The polystyrene 96-well plate was coated with TGF-β1 capture antibody (recognizing TGF-β1 C-terminus; Santa Cruz Biotech.).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, since MeNPs possess enzyme‐like activities, they can be utilized in the place of an enzyme in an enzyme‐linked immunosorbent assay (ELISA) to catalyze and activate the visualization reagent . Ahmed et al reported the detection of the influenza virus (H1N1) through the catalytic and enzymatic activity of a positive Au NPs ((+) Au NPs)‐based colorimetric immunoassay . According to this study, antibody‐modified (+) Au NPs possessed an activity similar to that of peroxidase, so this NP was used as an artificial enzyme instead of horseradish peroxidase (HRP) during the biosensing process.…”
Section: Plasmonic and Catalytic Nanoparticle‐based Biosensing Systemsmentioning
confidence: 99%